Genetic Variability in Kharchia Wheat (Triticum aestivum) from Salt Affected Areas in Rajasthan - Joshi, P (Annals of Arid Zone, 2016)
Kharchia wheat (Triticum aestivum) collections revealed signiricant variation for all the eight attributes including grain yield and rour indexes, both undernormal and saline conditions. Salt stress had maximum effect on number or grains spikelt-l due to high abortion in central florets. Three distinct mechanisms or salt tolerance were identified. Collections with high yield potential could be grouped in types with high susceptibility for spikelet index and those having poor grains/spikelet index. Third group included entries with low yield potential but performance at par under salinity due to internal cancellation in component performance. Suggestions for their utility in salt stress breading were made.